Smart contract architecture for decentralized energy trading and management based on blockchains - Han, Dong; Zhang, Chengzhenghao; Ping, Jian; Yan, Zheng (Energy (Oxford), 2020)
A blockchain-based smart contract has the potential to allow the performance of credible transactions without third parties. This paper presents a universal framework for a blockchain platform that enables peer-to-peer (P2P) energy trading in the retail electricity market. Focusing attention on seeking energy-matching pairs from the supply and demand sides, and encouraging direct energy trading between producers and consumers, the P2P energy trading mechanism is proposed. The designed multidimensional blockchain platform implements a complete energy trading process. As smart contracts strictly execute the trading and payment rules without human interaction, the security and fairness of energy trading are significantly enhanced. Case studies in the Ethereum private chain demonstrate that the proposed mechanism has obvious advantages in reflecting market quotations, balancing profits of players, and facilitating the utilization of renewables. Based on such characteristics, players are incentivized to participate in the P2P energy trading. Moreover, the authentic gas consumption and computational time to the smart contract indicate that this platform is able to achieve an efficient and effective transaction with multi-player participation. •This paper presented a P2P energy trading mechanism with the double auction.•A universal blockchain platform for decentralized energy trading was proposed.•The designed smart contract provides secure and automatic energy trading services.•Simulation results showed the feasibility and efficiency of the proposed platform.